2022
DOI: 10.1002/jeab.801
|View full text |Cite
|
Sign up to set email alerts
|

Nondrug reinforcers contingent on alternative behavior or abstinence increase resistance to extinction and reinstatement of ethanol‐maintained behavior

Abstract: The effects of delivering nondrug alternative reinforcement on resistance to extinction and reinstatement of rats' ethanol‐maintained lever pressing were evaluated in two experiments. In both, rats self‐administered ethanol by lever pressing in a two‐component multiple schedule during baseline. In the Rich component, alternative food reinforcement was made available for performing an alternative response (Experiment 1) or according to a differential‐reinforcement‐of‐other‐behavior schedule for lever pressing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Providing DRO reinforcement produced complete or near‐complete suppression of ethanol self‐administration for all rats. The DRO 5‐s schedule that was arranged initially for each rat was based on outcomes from a related study reported by Craig and Shahan (2022). These authors evaluated the effects of concurrently reinforcing rats' lever pressing and abstinence from lever pressing with ethanol and food reinforcement, respectively, on the resistance to extinction and reinstatement of lever pressing.…”
Section: Discussionmentioning
confidence: 99%
“…Providing DRO reinforcement produced complete or near‐complete suppression of ethanol self‐administration for all rats. The DRO 5‐s schedule that was arranged initially for each rat was based on outcomes from a related study reported by Craig and Shahan (2022). These authors evaluated the effects of concurrently reinforcing rats' lever pressing and abstinence from lever pressing with ethanol and food reinforcement, respectively, on the resistance to extinction and reinstatement of lever pressing.…”
Section: Discussionmentioning
confidence: 99%
“…Another core argument of behavioral momentum theory is that resistance to change is governed by the Pavlovian stimulus-reinforcer relation in a conditioning situation and that it is not affected by response-reinforcer relations. Empirical support for this argument is common (Nevin et al, 1990; see also Craig & Shahan, 2022;Mace et al, 2010;Podlesnik et al, 2012) across laboratories and species including pigeons, rats, fish, and people (see, e.g., Igaki & Sakagami, 2004;Mace et al, 1990;Podlesnik & Shahan, 2009;Shahan & Burke, 2004;Thrailkill et al, 2018). It is not, however, ubiquitous.…”
Section: Response-reinforcer Relationsmentioning
confidence: 99%
“…When an operant response produces the same rate of reinforcement in different discriminative‐stimulus contexts and additional response‐independent reinforcers are introduced into one of the contexts, two outcomes often are observed (Craig & Shahan, 2022; Grimes & Shull, 2001; Nevin et al, 1990; Shahan & Burke, 2004). First, baseline response rates tend to be lower in the context with added response‐independent reinforcers than in the context without the additional reinforcers (presumably because the response–reinforcer relation was disrupted by providing some portion of reinforcers gratis).…”
Section: Challenges To Behavioral Momentum Theorymentioning
confidence: 99%